1981
DOI: 10.1103/physrevlett.46.929
|View full text |Cite
|
Sign up to set email alerts
|

Instability of the Brillouin-Flow Equilibrium in Magnetically Insulated Structures

Abstract: experiment to realize the optical tristability in which sodium vapor is used as a dispersive medium. By filling He gas at pressure higher than 200 Torr as a buffer gas, y ab for D x line at 589.6 nm becomes larger than 2 GHz, 6 and we can neglect hole burning effect and hyperfine pumping especially for off-resonant light. Furthermore, the buffer gas mixes the excited hyperfine and Zeeman structure completely. Thus the situation is very close to the model which we have used in this paper. To satisfy the inequal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…However, as discussed in Sec. II B, a number of observations suggest that instabilities in the MITL's flow-electron plasma can result in electrostatic-and electromagnetic-field fluctuations, and that these can subject the electrons to effective collisions [16,21,22,24,28,29,33,. These observations imply that the frequency of such collisions can be sufficiently high to cause the flow electrons to have a small, but non-negligible, component of their drift velocities directed toward the anode.…”
Section: Introductionmentioning
confidence: 92%
“…However, as discussed in Sec. II B, a number of observations suggest that instabilities in the MITL's flow-electron plasma can result in electrostatic-and electromagnetic-field fluctuations, and that these can subject the electrons to effective collisions [16,21,22,24,28,29,33,. These observations imply that the frequency of such collisions can be sufficiently high to cause the flow electrons to have a small, but non-negligible, component of their drift velocities directed toward the anode.…”
Section: Introductionmentioning
confidence: 92%
“…The theory of non-neutral, laminar, E؋B drifting flows in crossed electric and magnetic fields has so far focused on the flow stability inside smooth wall cavities, [1][2][3][4][5][6] related to the magnetic gap insulation. In that context, the stability analysis of cathode layers ͑laminar flows touching the cathode͒ to short wavelength kdϾ1, slow wave /ckӶ1 perturbations has shown that ͑i͒ for an instability, both the Buneman Hartree Ϫku(x)ϭ0 and the cyclotron resonance Ϫku(x)ϭ⍀ must be satisfied at separate layers inside the flow ͑ii͒ the growth rate tends rapidly to zero 1,2 at the low space charge limit e 2 /⍀ 2 Ӷ1.…”
Section: Introductionmentioning
confidence: 99%
“…The truncation is obtained by assuming a certain characteristic for the system dynamics which is expressed by an equation of state. Perhaps, the simplest used approximation is the cold fluid, which completely neglects thermal effects by assuming a vanishing temperature [6][7][8][9][10][11][12]. Other examples of largely used equations of state are isothermal [13][14][15][16][17] and adiabatic [18,19].…”
mentioning
confidence: 99%